Invasive Candida krusei infection and Candida vasculitis of a leg ulcer in an immunocompetent patient: A case report. (February 2017) - Jud, Philipp; Valentin, Thomas; Regauer, Sigrid; Gary, Thomas; Hackl, Gerald; Rief, Peter; Brodmann, Marianne; Hafner, Franz
Abstract: A 71 year old female Caucasian farmer without any known immunosuppression presented with a painful ulcer of her right lower leg after a trauma caused by a wood billet. There was no response to empirical antibacterial treatment. An ulcer biopsy showed an invasive Candida infection of the soft tissue and leucocytoclastic vasculitis. Voriconazole treatment was followed by wound healing. Invasive Candida infection and localized Candida vasculitis represent a rare cause of persisting leg ulcers. The similar clinical picture of chronic venous leg ulcers might blur the true cause and refractory cases should therefore promptly be processed by histopathological diagnostics.